Effect of a wearable patient sensor on care delivery for preventing pressure injuries in acutely ill adults: A pragmatic randomized clinical trial (LS-HAPI study). (April 2018) - Pickham, David; Berte, Nic; Pihulic, Mike; Valdez, Andre; Mayer, Barbara; Desai, Manisha
Abstract: Importance: Though theoretically sound, studies have failed to demonstrate the benefit of routine repositioning of at-risk patients for the prevention of hospital acquired pressure injuries. Objective: To assess the clinical effectiveness of a wearable patient sensor to improve care delivery and patient outcomes by increasing the total time with turning compliance and preventing pressure injuries in acutely ill patients. Design: Pragmatic, investigator initiated, open label, single site, randomized clinical trial. Setting: Two Intensive Care Units in a large Academic Medical Center in California. Participants: Consecutive adult patients admitted to one of two Intensive Care Units between September 2015 to January 2016 were included (n = 1564). Of the eligible patients, 1312 underwent randomization. Intervention: Patients received either turning care relying on traditional turn reminders and standard practices (control group, n = 653), or optimal turning practices, influenced by real-time data derived from a wearable patient sensor (treatment group, n = 659). Main outcome(s) and Measure(s): The primary and secondary outcomes of interest were occurrence of hospital acquired pressure injury and turning compliance. Sensitivity analysis was performed to compare intention-to-treat and per-protocol effects. Results: The mean age was 60 years (SD, 17 years); 55% were male. We analyzed 103, 000 h of monitoring data. Overall the intervention group had significantly fewer Hospital Acquired Pressure Injuries during Intensive Care Unit admission than the control group (5 patients [0.7%] vs. 15 patients [2.3%] ( OR = 0.33, 95%CI [0.12, 0.90], p = 0.031). The total time with turning compliance was significantly different in the intervention group vs. control group (67% vs 54%; difference 0.11, 95%CI [0.08, 0.13], p < 0.001). Turning magnitude (21°, p = 0.923) and adequate depressurization time (39%, p = 0.145) were not statistically different between groups. Conclusions and Relevance: Among acutely ill adult patients requiring Intensive Care Unit admission, the provision of optimal turning was greater with a wearable patient sensor, increasing the total time with turning compliance and demonstrated a statistically significant protective effect against the development of hospital acquired pressure injuries. These are the first quantitative data on turn quality in the Intensive Care Unit and highlight the need to reinforce optimal turning practices. Additional clinical trials leveraging technologies like wearable sensors are needed to establish the appropriate frequency and dosing of individualized turning protocols to prevent pressure injuries in at-risk hospitalized patients.